THE HANDLING OF HUMAN TRAFFICKING WITH MAIL ORDER BRIDE MODE IN WEST KALIMANTAN - Yenny AS; Anita Yuliastini; Rini Setiawati (UNISSULA, 2020)
Trafficking especially women and children in West Kalimantan, is still vulnerable in various modes, including through order bride. Factors that influence the trafficking include poverty, lack of education, limited employment, patriarchal culture, and weak law enforcement as well as mechanisms and coordination of handling trafficking. This article will explore the issue of trafficking with the mail order bride mode by revealing the problem of what factors are obstacles in law enforcement handling the crime of trafficking in persons with the order bride mode. This article will explore the issue of handling the trafficking with the order bride mode by revealing the problem of what factors are obstacles in law enforcement handling the crime of trafficking in persons with the mail order bride mode. Through the socio-legal research method with a qualitative approach, the research results are obtained that the obstacles faced in handling criminal acts of trafficking with the mail order bride mode are still weak cooperation and coordination between relevant agencies and law enforcement officials, especially these crimes occur in transnational networks.